Ruthenium(II)-Catalyzed C–H Annulation of Mandelic Acids with Internal Alkynes to Construct Isocoumarins - Li, Shen Min; Wang, Wang Huai; Li, Hong Jiang; Du, Fang; Cui, Ying Na; Zhang, Shu Jia (Synlett, 2023)
A series of isocoumarins were synthesized by a one-pot cyclization reaction with mandelic acids and internal alkynes as raw materials, [RuCl2(p-cymene)]2 as a catalyst, and Cu(OAc)2·H2O as an oxidant under reflux conditions in air. By using the established efficient and reliable reaction conditions, a range of substrates were explored, and it was found that both aromatic aldehydes and aromatic acids also reacted smoothly in this system to give moderate yields of the target products. Furthermore, the mandelic acids were shown to be converted into the corresponding benzoic acids as intermediates in the reaction.
Keywords: ruthenium catalysis; mandelic acids; alkynes; annulation; isocoumarins